A Survey as to the Content of the Introductory POM Course - Berry, Stephen E.; Watson, Hugh J.; Greenwood, William T. (Academy of Management Journal, 1978)
Academicians and practitioners were surveyed as to what should be taught in the introductory Production/Operations Management (POM) course. Study results indicate practitioners feel that the course should be more ?concept? than ?technique? oriented, while academicians feel that the mix should be more evenly split. Findings are discussed in terms of their implications for curriculum design.